Let's talk French. (Syracuse, N.Y. Syracuse Language Systems, 1995)
SUMMARY: facilities learning over 2,200 French words grouped alphabetically and by subject. Speech recognition feature and record/ playback function help the user improve pronounciation. Includes photographs, games, exercises and French-English glossary.
System requirements: IBM-Compatible computer with a 486 DX/33 MHZ processor (or better); 8 MB RAM; Windows 3.1 or Windows 95; SVGA graphics display (640 x 480 resolution and 256 colors); hard disk with BMB free space; CD-ROM drive; sixteen-bit sound card; speakers or headphones mouse.
Title from disks label
"A Random House/ Syracuse Language System Program.
Keywords: French language -- Vocabulary -- Software; French language -- Pronounciation -- Software; French language -- Computer-assisted instruction for foreign speakers -- Software